Bortezomib in the treatment of refractory kidney graft rejection - Farinha,Ana (2012)
Background. Bortezomib, a 26S proteasome inhibitor, is a novel treatment for refractory acute rejection. The main mechanism proposed for its action is the induction of apoptosis of mature plasma cells leading to an interruption of donor-specific antibody production, but other properties may also be involved. Patients and Methods. Four patients presenting with antibody-mediated rejection were treated with bortezomib as rescue therapy. Renal function, proteinuria and anti-HLA antibodies were monitored for 1-3 years. Results. In three cases, graft function recovery and decreased proteinuria occurred, despite the maintenance of donor-specific antibody levels. However, in one case graft function was lost. Side effects were mostly transient. There were no episodes of opportunistic infection. Conclusion. Bortezomib may be effective in antibodymediated rejection by different mechanisms than simply through reducing donor-specific antibody levels. The timing of its introduction and the length of time that donor-specific antibodies have been present may be determinants of its efficacy